Hay fever & homeopathy: a case series evaluation. Issue 2 (May 2016) - Pandey, Vinita
Abstract : Background: Seasonal allergic rhinitis (hay fever) is common and can considerably reduce the quality of life of sufferers. Despite the wide everyday application and promising results with homeopathy, scientific evidence of its effectiveness for most ailments is scarce. Aim: The assessment of the clinical effectiveness of homeopathic remedies in the alleviation of hay fever symptoms in a typical clinical setting. Methods: We performed a clinical observational study of eight patients in the treatment of hay fever symptoms over a two-year period (2012 and 2013) using Measure Yourself Medical Outcome Profile (MYMOP) self-evaluation questionnaires at baseline and again after two weeks and four weeks of homeopathic treatment. The individualized prescription – either a single remedy or multiple remedies – was based on the totality of each patient's symptoms. Results: The average MYMOP scores for the eyes, nose, activity and wellbeing had improved significantly after two and four weeks of homeopathic treatment. The overall average MYMOP profile score at baseline was 3.83 (standard deviation, SD, 0.78). After 14 and 28 days of treatment the average score had fallen to 1.14 (SD, 0.36; P < 0.001) and 1.06 (SD, 0.25; P < 0.001) respectively. Conclusions: Individualized homeopathic treatment was associated with significant alleviation of hay fever symptoms, enabling the reduction in use of conventional treatment. The results presented in this study can be considered as a step towards a pilot pragmatic study that would use more robust outcome measures and include a larger number of patients prescribed a single or a multiple homeopathic prescription on an individualized basis. Graphical abstract: Timings of the assessments: Hay fever season every year lasts from April to October in the UK. The patients visited Health Zone Clinic in year 2012 are represented by while the same patients in 2013 are represented by . 1st appointment (baseline assessment) is represented by red dot while 2nd and 3rd appointments are represented by dark green dots. Telephonic consultation for each patient in late August/September is represented by light green dots. The red dots indicate high MYMOP scores while the dark green dots indicate low MYMOP scores, hence the improvement in hay fever symptoms using homeopathy. Highlights: A clinical observational study in the treatment of hay fever symptoms. MYMOP questionnaires were used for patient-reported outcome. Homeopathy treatment was associated with significant alleviation of hay fever symptoms. All patients reported reducing the use of conventional medicines. The results of this study indicate towards a future pilot pragmatic study.